1 MILO/ENGOT-OV11: Phase-3 study of binimetinib versus physician's choice chemotherapy (PCC) in recurrent or persistent low-grade serous carcinomas of the ovary, fallopian tube, or primary peritoneum. (18th September 2019) - Grisham, R; Monk J, B; Banerjee, S; Coleman L, R; Oza M, A; Oehler K, M; Kalbacher, E; Mirza Raza, M; del Campo M, J; Marth, C; Westermann, A; Pignata, S; et al.
Abstract : Objectives: Low-grade serous ovarian carcinomas (LGSOC) have historically low chemotherapy responses. Alterations affecting the MAPK pathway, most commonly KRAS/BRAF, are present in 30–60% of LGSOC. A phase II study of the MEK inhibitor selumetinib showed promising response rate of 15% in LGSOC and binimetinib, a potent MEK1/2 inhibitor, has demonstrated activity across multiple cancers. Methods: MILO (MEK-Inhibitor in Low-grade Serous Ovarian Cancer)/ENGOT-ov11 was an open-label, 2:1-randomized study of binimetinib (45-mg BID) vs PCC in LGSOC. Eligible patients had recurrent or persistent measurable LGSOC following ≥1 prior platinum-based chemotherapy, ≤3 prior chemotherapy lines, and no prior MEK-or BRAF-inhibitor. The primary endpoint was progression-free survival (PFS) by blinded central review; additional assessments: overall survival (OS), overall response rate (ORR), duration of response (DOR), clinical-benefit rate, biomarkers, and safety.(NCT01849874 ). Results: 303 patients were randomized (201 binimetinib, 102 PCC). Median PFS was 9.1 months (95% CI:7.3, 11.3) for binimetinib and 10.6 months (95% CI:9.2, 14.5) for PCC (HR:1.21(0.79, 1.86);closed early for futility). Secondary efficacy endpoints were similar in the two groups: ORR 16%(complete/partial responses[CR/PRs]=32) vs 13%(CR/PRs=13); median DOR 8.1 (range:0.3–12.0+ months) vs 6.7 (0.3–9.7+ months); and median OS 25.3 vs 20.8 months, for binimetinib and PCC, respectively. Safety results were consistent with known safety profile of binimetinib; most common ≥grade 3 events were blood CK increased(20%) and hypertension(20%). Post-hoc analysis suggests a possible association between KRAS mutation and response to binimetinib. Conclusions: Although MILO did not meet its primary endpoint, binimetinib showed activity in LGSOC across the efficacy endpoints evaluated. Chemotherapy responses were higher than predicted. Further evaluation is warranted.